Hemodynamic effects of heart rate lowering in patients admitted for acute heart failure: the RedRate-HF Study (Reduction of heart Rate in Heart Failure). Issue 2 (February 2023) - Mortara, Andrea; Rossi, Jessica; Mazzetti, Simone; Catagnano, Francesco; Cavalotti, Cristina; Malerba, Gianluigi; Vecchio, Chiara; Morandi, Fabrizio; Nassiacos, Daniele; Oliva, Fabrizio
Abstract : Background: In patients admitted for acute heart failure (HF) indication for drugs which reduce the heart rate (HR) is debated. The multicentre prospective study Reduction of heart Rate in Heart Failure (RedRate-HF) was designed to analyse the hemodynamic effects of an early reduction of HR in acute HF. Methods: Hemodynamic parameters were recorded by using the bioimpedance technique, which was shown to be accurate, highly reproducible and sensitive to intra-observer changes. Lowering HR was obtained by ivabradine 5 mg bd, given 48–72 h after admission on the top of optimized treatment. Patients were followed at 24, 48, 72 h after drug assumption and at hospital discharge. Results: Twenty patients of a mean age of 67 ± 15 years, BNP at entry 1348 ± 1198 pg/ml were enrolled. Despite a clinical stabilization, after 48–72 h from admission, HR was persistently >70 bpm. Ivabradine was well tolerated in all patients with a significant increase in RR interval from 747 ± 69 ms at baseline to 948 ± 121 ms at discharge, P  < 0.0001. Change in HR was associated with a significant increase in stroke volume (baseline 73 ± 22 vs. 84 ± 19 ml at discharge, P  = 0.03), and reduction in left cardiac work index (baseline 3.6 ± 1.2 vs. 3.1 ± 1.1 kg/m 2 at discharge, P  = 0.04). Other measures of heart work were also significantly affected while cardiac output remained unchanged Conclusion: The strategy of an early lowering of HR in patients admitted for acute HF on top of usual care is feasible and safe. The HR reduction causes a positive increase in stroke volume and may contribute to saving energy without affecting cardiac output.